2019
DOI: 10.1111/codi.14888
|View full text |Cite
|
Sign up to set email alerts
|

The Portsmouth protocol for intra‐operative ultrasound of the small bowel in Crohn's disease

Abstract: Aim Bowel preservation is paramount in Crohn's disease surgery as affected patients are typically young adults at risk of having several abdominal surgical procedures during their lifetime. Intra‐operative assessment of the extent and location of Crohn's disease is not standardized and is left to a mixture of the surgeon's experience, tactile feedback, macroscopic appearance and preoperative imaging. The aim of this study was to describe the technical steps of a standardized protocol for intra‐operative ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…We included patients with CD affecting the small bowel requiring elective surgical treatment, according to the following inclusion criteria: (1) Aged 18 years or over; (2) American Society of Anaesthesiologists (ASA) grade I, II or III; (3) Undergoing elective surgery to remove part of the terminal ileum which is affected by CD; (4) Indication for surgery agreed at inflammatory bowel disease (IBD) multidisciplinary team (MDT) meeting; (5) Able to give written informed consent.…”
Section: Study Settings and Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…We included patients with CD affecting the small bowel requiring elective surgical treatment, according to the following inclusion criteria: (1) Aged 18 years or over; (2) American Society of Anaesthesiologists (ASA) grade I, II or III; (3) Undergoing elective surgery to remove part of the terminal ileum which is affected by CD; (4) Indication for surgery agreed at inflammatory bowel disease (IBD) multidisciplinary team (MDT) meeting; (5) Able to give written informed consent.…”
Section: Study Settings and Eligibility Criteriamentioning
confidence: 99%
“…Moreover, incorrect intraoperative mapping of the extent of disease may mislead the multidisciplinary team in decision making about postoperative maintenance treatment. To overcome this variability, we developed a protocol for full intraoperative ultrasound scan (USS) of the small bowel [2]. The aim of this study was to report the results of the feasibility study "Assessing the Feasibility and Safety of Using Intraoperative Ultrasound in Ileocolic Crohn's Disease-The IUSS CROHN Study".…”
Section: Introductionmentioning
confidence: 99%
“…In our IBD Unit we are currently developing a prospective study with focus on MRE defined sarcopenia and functional assessment of muscle function, also including a psoas muscle assessment at intestinal USS as part of an experimental pre and intraoperative dedicated USS protocol. [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, an intraoperative lesion search will also require technological progress without relying on the experience and inspection ability of the attending surgeon. In this regard, Celentano V et al reported the usefulness of an intraoperative ultrasound examination of the small bowel in Crohn's disease patients [9].…”
Section: Discussionmentioning
confidence: 99%